COVID-19 Lockdown and Its Adverse Impact on Psychological Health in Breast Cancer - Swainston, Jessica; Chapman, Bethany; Grunfeld, Elizabeth A.; Derakshan, Nazanin (Frontiers in Psychology, 2020)
The Coronavirus disease 2019 (COVID-19) outbreak generated an unprecedented set of emotional challenges for women diagnosed with breast cancer. In the UK, the pandemic significantly disrupted oncology services as resources were reassigned to care for COVID-19 patients. In addition to service disruptions, many women received a UK Government letter advising them to shield for 12-weeks. We aimed to explore the effect of disruption to scheduled oncology services and the UK Government shielding letter on emotional and cognitive vulnerability. A further aim was to investigate the relationship between COVID-19 related emotional vulnerability (COVID-EMV) and anxiety, depression and perceived cognitive function. Women diagnosed with primary breast cancer (N = 234) completed a series of online questionnaires to assess their cognitive and emotional wellbeing as well as their COVID-EMV. Results indicated that disrupted oncology services had a significant impact on COVID-EMV, anxiety and depression, with those experiencing disruptions expressing higher general emotional vulnerability as well as COVID-EMV. Further, the UK Government letter had a significant effect on perceived cognitive function; those who received the letter reported poorer cognitive function. Regression analyses revealed that after allowing for the effects of sociodemographic and clinical variables, women’s COVID-EMV significantly predicted worse outcomes of anxiety, depression and perceived cognitive function. Our findings indicate that concerns about COVID-19 amongst women affected by breast cancer leads to increased risk of developing affective disorder, such as anxiety and depression symptomatology, among this sample. We advocate the rapid implementation of accessible interventions designed to promote emotional resilience in the breast cancer population.